Modulation of smoke-induced DNA and microRNA alterations in mouse lung by licofelone, a triple COX-1, COX-2 and 5-LOX inhibitor. (28th September 2019) - Izzotti, Alberto; Balansky, Roumen; Micale, Rosanna T; Pulliero, Alessandra; La Maestra, Sebastiano; De Flora, Silvio
Abstract: Chronic inflammation plays a crucial role in the carcinogenesis process and, in particular, in smoking-related carcinogenesis. Therefore, anti-inflammatory agents provide an interesting perspective in the prevention of smoking-associated cancers. Among nonsteroidal anti-inflammatory drugs (NSAIDs), licofelone is a triple inhibitor of both cyclooxygenases (COX-1 and COX-2) and of 5-lipooxygenase (5-LOX) that has shown some encouraging results in cancer prevention models. We previously showed that the dietary administration of licofelone, starting after weanling, to Swiss H mice exposed for 4 months to mainstream cigarette smoke since birth attenuated preneoplastic lesions of inflammatory nature in both lung and urinary tract, and had some effects on the yield of lung tumors at 7.5 months of age. The present study aimed at evaluating the early modulation by licofelone of pulmonary DNA and RNA alterations either in smoke-free or smoke-exposed H mice after 10 weeks of exposure. Licofelone protected the mice from the smoke-induced loss of body weight and significantly attenuated smoke-induced nucleotide alterations by decreasing the levels of bulky DNA adducts and 8-hydroxy-2′-deoxyguanosine in mouse lung. Moreover, the drug counteracted dysregulation by smoke of several pulmonary microRNAs involved in stress response, inflammation, apoptosis, and oncogene suppression. However, even in smoke-free mice administration of the drug had significant effects on a broad panel of microRNAs and, as assessed in a subset of mice used in a parallel cancer chemoprevention study, licofelone even enhanced the smoke-induced systemic genotoxic damage after 4 months of exposure. Therefore, caution should be paid when administering licofelone to smokers for long periods. Abstract : Licofelone, inhibitor of COX-1, COX-2 and 5-LOX, protected smoke-exposed mice from pulmonary nucleotide alterations (DNA adducts and 8-hydroxy-2′-deoxyguanosine) and counteracted dysregulation of several microRNAs. However, even in smoke-free mice the drug dysregulated a broad panel of microRNAs.